Matrimonial reliefs to Muslim divorced women in the State of Selangor / Suguram Bibi Munshi Deen - Munshi Deen, Suguram Bibi (Faculty of Law, 1982)
The purpose of this paper is to highlight some of the outstanding rights of muslim women on divorce. There is a call by the muslim women in Malaysia for the implementation of a fairer and uniform muslim law in Malaysia. In the year 1975, the First Muslim Women's Convention was held where more than four hundred muslim women representing twenty organisation contended that: - "The principals of the Islamic Family Law as laid down in the Quaran and Prophet's sayings (hadith) are just; but the practise in Malaysia falls seriously short of these principles.” Therefore the convention pressed for reforms and fairer implementation of the Muslim Law relating to marriage and divorce. The significants of this convention is that for the very first time in the history of Malaysia the muslim women seems to say: - "Look, we are united, we know our rights in Islam we want, those rights to be upheld." However, women of Malaysia due to lack of education, poverty and other factors are still ignorant of their full rights under Islam. At the convention stated above, a few women who participated in this convention have never heard of the payment of MUTA’AH which is a consolatory gifts made by the husband to the wife if she is divorced without just cause.